Output spillovers from U.S. monetary policy: The role of international trade and financial linkages - Falk Bräuning; Viacheslav Sheremirov (Federal Reserve Bank of Boston, 2019)
We estimate that U.S. monetary policy has sizable spillover effects on global economic activity. In response to a surprise increase in the federal funds rate of 25 basis points, real output in our sample of 44 countries declines on average by 0.9% after three years. We find that international trade is a more important factor than international finance in explaining these spillovers. In particular, countries with a high share of exports and imports in output have 79% larger responses than countries with a low share, whereas we do not find significant heterogeneity depending on a country's financial openness. Bilateral trade linkages appear to be quantitatively important, as the network amplification effect accounts for 45% of the total spillover effect at the peak horizon. We conclude that trade networks could be an important ingredient of theoretical models focusing on the international effects of U.S. monetary policy shocks.
Keywords: E52; F42; F44; G15; 330; financial linkages; international spillovers; monetary shocks; trade networks